Applying the standardized infection ratio for reporting surgical site infections in Australian healthcare facilities - Stephanie K. Tanamas; Lyn-Li Lim; Ann L. Bull; Michael J. Malloy; Allen C. Cheng; Leon J. Worth (Cambridge University Press, 2023)
Abstract Objective: We explored the utility of the standardized infection ratio (SIR) for surgical site infection (SSI) reporting in an Australian jurisdiction. Design: Retrospective chart review. Setting: Statewide SSI surveillance data from 2013 to 2019. Patients: Individuals who had cardiac bypass surgery (CABG), colorectal surgery (COLO), cesarean section (CSEC), hip prosthesis (HPRO), or knee prosthesis (KPRO) procedures. Methods: The SIR was calculated by dividing the number of observed infections by the number of predicted infections as determined using the National Healthcare Safety Network procedure-specific risk models. In line with a minimum precision criterion, an SIR was not calculated if the number of predicted infections was <1. Results: A SIR >0 (≥1 observed SSI, predicted number of SSI ≥1, no missing covariates) could be calculated for a median of 89.3% of reporting quarters for CABG, 75.0% for COLO, 69.0% for CSEC, 0% for HPRO, and 7.1% for KPRO. In total, 80.6% of the reporting quarters, when the SIR was not calculated, were due to no observed infections or predicted infections <1, and 19.4% were due to missing covariates alone. Within hospitals, the median percentage of quarters during which zero infections were observed was 8.9% for CABG, 20.0% for COLO, 25.4% for CSEC, 67.3% for HPRO, and 71.4% for KPRO. Conclusions: Calculating an SIR for SSIs is challenging for hospitals in our regional network, primarily because of low event numbers and many facilities with predicted infections <1. Our SSI reporting will continue to use risk-indexed rates, in tandem with SIR values when predicted number of SSI ≥1.